Associations between parents' perception of neighbourhood environments and safety with physical activity of primary school children in Klang, Selangor, Malaysia - Tung, S. E. H.; Ng, X. H.; Chin, Y. S.; Mohd Taib, M. N. (Wiley-Blackwell Publishing, 2016)
BACKGROUND:This study aimed to evaluate parental perception of neighbourhood environments and safety in association with children's physical activity among primary school children in Klang, Selangor, Malaysia.